Development of modified RSA algorithm using fixed mersenne prime numbers for medical ultrasound imaging instrumentation. (7th October 2019) - Shin, Seung-Hyeok; Yoo, Won Sok; Choi, Hojong
Abstract: Purpose: Encryption of patient information has become an important issue in medical ultrasound instrumentation to secure information when images are accessed off-site. The proposed algorithm is used to encrypt private medical images and transfer the encrypted images to improve the encryption capability and elapsed time. Materials and methods: We generate a public key using three prime numbers, including a fixed Mersenne prime number, in the modified Rivest-Shamir-Adelman (RSA) algorithm to compare the encryption capability. We calculated and compared the elapsed time using the modified RSA algorithm with a breast phantom in the medical ultrasound imaging instrumentation. Results: The encryption capability is improved because the elapsed time when using three prime numbers is longer (1.2337 s) than that when using two prime numbers (1.0712 s). However, the elapsed time using fixed Mersenne prime numbers (0.8360 s) is a similar to that using two prime numbers (0.8389 s). Conclusions: Our proposed cryptographic algorithm provides improved encryption in medical ultrasound imaging compared to algorithms that use two prime numbers that are not Mersenne prime numbers, while transmitting images with adequate elapsed times.